Low plasma D‐dimer predicts absence of intracranial injury and skull fracture. Issue 1 (6th January 2020) - Nozawa, Masahiro; Mishina, Hiroki; Tsuji, Satoshi; Takayama, John I
Abstract: Background: Intracranial injury (ICI) is a leading cause of morbidity in children; however, the use of computed tomography (CT) to evaluate ICI has significant risks in children. A recent study suggests D‐dimer is associated with ICI. We surveyed the performance of plasma D‐dimer in ruling out ICI or skull fracture (SF) in children with head trauma. Methods: In a cross‐sectional study in the Emergency Department (ED) at the National Center for Child Health and Development in Tokyo, Japan we reviewed the medical records of all children age 0–16 years brought to the ED with head trauma from January 2010 to July 2013, who underwent CT based on established clinical criteria and had plasma D‐dimer measured. We evaluated sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) of plasma D‐dimer, using abnormal findings on CT (ICI, SF) as the criterion standard. We repeated analysis after stratification by age (<2 years, ≥2 years). Results: Among 364 eligible children (112 children <2 year of age), abnormal findings on CT were demonstrated in 33.8% (123/364). With the cut‐off set at 0.5 μg/mL, sensitivity was 100.0% (95% confidence interval [CI]: 95.6–100.0%), specificity 34.0% (95%CI: 28.1–40.4%), PPV 43.6% (95%CI: 37.7–49.6%), NPV 100.0% (95%CI: 93.5–100%). After stratification by age (<2 years and ≥2 years), sensitivity (100.0% and 100.0%) and NPV (100.0% and 100.0%) remained high in both age groups. Conclusions: Low plasma D‐dimer (≤0.5 μg/mL) is useful to limit the use of CT in children by excluding traumatic ICI or SF.